LEGAL ASPECTS OF IMPLEMENTING SALES OF ELECTRICITY SERVICES IN INDONESIA CARRIED OUT BY PT. PLN TO CONSUMERS - Novita, Mayang Sari (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
One of the national scale needs is the availability of electric power for various purposes. However, the problem that arises is that there are consumers who feel disadvantaged due to the electricity cut off by PT. PLN as the provider of electricity services to consumers. The formulation of the research problem is what are the legal aspects of implementing the sale of electricity services in Indonesia carried out by PT. PLN to Consumers?, What are the factors that cause civil disputes between electricity service providers PT. PLN with Consumers?, and How to resolve the problem of electricity disconnection carried out by PT. PLN towards consumers? This research is empirical juridical research, which in other words is a type of sociological legal research and can also be called field research, namely studying the applicable legal provisions and what happens in reality in the field or in society by conducting interviews at BPSK Medan City related to research title. In this research it can be concluded that the legal aspects of implementing the sale of electricity services in Indonesia carried out by PT. PLN to Consumers is an aspect of the requirements for the legal sale and purchase of electricity services in Indonesia carried out by PT. PLN to consumers who must follow the conditions for the validity of the agreement as in Article 1320 of the Civil Code, Factors causing civil disputes between electricity service providers PT. PLN with consumers is due to the factor that one of the parties is in default and the factor that there is an unlawful act, and Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection is an embodiment of consumer protection in Indonesia and Business Actors